2004
DOI: 10.1590/s1519-566x2004000400015
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição espacial de Bemisia tabaci (Genn.) biótipo B (Hemiptera: Aleyrodidae) em feijoeiro (Phaseolus vulgaris L.)

Abstract: -The study of spatial distribution of the insects is fundamental to elaborate sampling plans with potential for use in integrated pest management. Field experiments were carried out for Bemisa tabaci B biotype in common bean Phaseolus vulagaris L. in a 10,000 m 2 area, divided in 100 equal 10 x 10 m plots, at the November and February plantings. Ten plants per plot were sampled weekly. One foliole per plant was collected and the presence-absence of whitefly nymphs was assessed on the abaxial surface. For adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
7
0
4
Order By: Relevance
“…It causes economic losses in vegetable, fi ber, and ornamental crops due to both direct damage through phloem feeding and injection of toxins and indirect damage to the host plant through its ability to transmit plant viruses (Pereira et al 2004;Brown 2010). Th e direct damage elicited by B. tabaci has a vast impact on plant health and consequently yield.…”
Section: Introductionmentioning
confidence: 99%
“…It causes economic losses in vegetable, fi ber, and ornamental crops due to both direct damage through phloem feeding and injection of toxins and indirect damage to the host plant through its ability to transmit plant viruses (Pereira et al 2004;Brown 2010). Th e direct damage elicited by B. tabaci has a vast impact on plant health and consequently yield.…”
Section: Introductionmentioning
confidence: 99%
“…Their spatial distribution, defined as the position that individuals occupy in space relative to each another, at a given focus (Vieira, 2000), influ-ences insect population dynamics. Differences in structure can be observed in relation to the sampled area, crop where they live (Knudsen et al, 1994), species (Nestel & Klein, 1995), and developmental stage (Farias et al, 2001;Pereira et al, 2004). Insect spatial distribution studies have been performed using geostatistical analysis (Midgarden et al, 1993;Nestel & Klein, 1995;Ellsbury et al, 1998;Pereira et al, 2004) and have shown that random distribution patterns rarely occur in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in structure can be observed in relation to the sampled area, crop where they live (Knudsen et al, 1994), species (Nestel & Klein, 1995), and developmental stage (Farias et al, 2001;Pereira et al, 2004). Insect spatial distribution studies have been performed using geostatistical analysis (Midgarden et al, 1993;Nestel & Klein, 1995;Ellsbury et al, 1998;Pereira et al, 2004) and have shown that random distribution patterns rarely occur in nature. According to Jesus et al (2002), the aggregate type of distribution is predominant, since these patterns are influenced by specific differences in each environment.…”
Section: Introductionmentioning
confidence: 99%
“…Como plantas de feijoeiro com B. tabaci biótipo B apresentam distribuição regular no campo, independente do estágio de desenvolvimento da cultura e da época de semeadura (Pereira 2002), o plano de amostragem seqüencial proposto pode ser utilizado durante todo o desenvolvimento vegetativo do feijoeiro, bem como em diferentes épocas de semeadura. Obviamente, o plano deve ser indicado de acordo com o ataque da praga à cultura e os prejuízos causados, seguindo as recomendações preconizadas pelo MIP.…”
Section: Resultsunclassified